OPTIMASI LAMA PERENDAMAN LARUTAN BUAH BELIMBING WULUH (Averrhoa bilimbi L) TERHADAP DAYA TETAS TELUR IKAN NILA (Tilapia nilotica) - Abdul Malik; Inriyani Inriyani (OCTOPUS : JURNAL ILMU PERIKANAN, 2015)
The purpose of this study was to determine the soaking time optimization solution star fruit (Averrhoa bilimbi L) on the hatchability of eggs tilapia (Tilapia nilotica). The method used is the tilapia eggs obtained from Fish Seed Center (BBI) which is derived from natural pemijahaan. Eggs are used as much as 50 grains / container research. Total container study 12 units with a capacity of each container as much as 5 liters of water. Research container filled with water 1 liter. The treatments tested was the star fruit soaking solution with different doses in preventing bacteria and fungus on eggs tilapia. In this study there were 4 treatment, soaking time 5 minutes (treatment A), soaking time 10 minutes (treatment B), soaking time 15 minutes (treatment C), without soaking solution of star fruit (treatment D). With each dose (A, B and C) 4000 ppm treatment. Research carried out for 1 month showed that hatchability is highest in treatment B is a 10-minute soaking time average hatchability of 93.33%. It is advisable to test the 10-minute soaking time by increasing the density of eggs. Also in the hatchery, water quality should be in decent conditions in the development of the eggs to become larvae.